Flexible Supercapacitors: A Materials Perspective - Palchoudhury, Soubantika; Ramasamy, Karthik; Gupta, Ram K.; Gupta, Arunava (Frontiers in Materials, 2019)
Flexible supercapacitors are highly attractive for the large number of emerging portable lightweight consumer devices. The novelty of a flexible supercapacitor is the incorporation of flexible electrode or substrate material to combine structural flexibility with the inherently high power density of supercapacitors. Flexible supercapacitors can use non-Faradaic energy storage process as seen in the electric double layer capacitor type or a Faradaic mechanism as seen in the pseudocapacitors. In this review, we account the current progress in pseudocapacitive electrode materials, fabrication techniques and new materials for electric double layer capacitor, and different flexible substrates. Future directions in developing new materials towards improved energy density and cost-effectiveness of the flexible supercapacitors and their usage in combination with lithium-ion batteries are highlighted.